25-Hydroxyvitamin D and Long Menstrual Cycles in a Prospective Cohort Study. Issue 3 (May 2018) - Jukic, Anne Marie Z.; Wilcox, Allen J.; McConnaughey, D. Robert; Weinberg, Clarice R.; Steiner, Anne Z.
Abstract : Background: Vitamin D insufficiency is associated with subfertility and prolonged estrus cycles in animals, but humans have not been well studied. Methods: A prospective time-to-pregnancy study, Time to Conceive (2010–2015), collected up to 4 months of daily diary data. Participants were healthy, late reproductive-aged women in North Carolina who were attempting pregnancy. We examined menstrual cycle length as a continuous variable and in categories: long (35+ days) and short (⩽25 days). Follicular phase length and luteal phase length were categorized as long (18+ days) or short (⩽10 days). We estimated associations between those lengths and serum 25-hydroxyvitamin D (25[OH]D) using linear mixed models and marginal models. Results: There were 1, 278 menstrual cycles from 446 women of whom 5% were vitamin D deficient (25[OH]D, <20 ng/ml), 69% were between 20 and 39 ng/ml, and 26% were 40 ng/ml or higher. There was a dose–response association between vitamin D levels and cycle length. Compared with the highest 25(OH)D level (≥40 ng/ml), 25(OH)D deficiency was associated with almost three times the odds of long cycles (adjusted odds ratio [aOR] = 2.8 [95% confidence interval (CI) = 1.0, 7.5]). The aOR was 1.9 (1.1, 3.5) for 20 to <30 ng/ml. The probability of a long follicular phase and the probability of a short luteal phase both increased with decreasing 25(OH)D. Conclusions: Lower levels of 25(OH)D are associated with longer follicular phase and an overall longer menstrual cycle. Our results are consistent with other evidence supporting vitamin D's role in the reproductive axis, which may have broader implications for reproductive success. Abstract : Supplemental Digital Content is available in the text.